Assessment of joint hazard to the outer environment from road and industrial noise by the example of the Katowice voivodeship - KOMPAŁA, J. (Archives of Acoustics, 1998)
An analysis of available professional papers on the subject shows that, in spite of the fact that some theoretical base exist, there is no general formulation of the problem discussed in this study. This is reason for undertaking the task and making a quantitative analysis of acoustic climate for the Katowice voivodeship. This paper is a report on the first attempt in Poland to work out an acoustic map which takes into consideration all traffic and industrial sources of noise located in a large and diversified area. The purpose of this paper is create on acoustic map of Katowice voivodeship and quantitative analysis of acoustic climate which takes into consideration noise of industrial and transportation.